Pembelajaran Sains Melalui Mini Praktikum untuk Anak Usia Dini dan Usia Sekolah di Rumah Pintar Kreatif Ampang, Kelurahan Ampang, Sumatera Barat - Fatridha Yansen; Eldya Mossfika; Linda Elfia (Prosiding, 2023)
Science has an important role in improving the quality of human life and has significant positive effects on the development of children’s personality and potential. However, many people believe that science is a challenging field of study. Therefore, it is important to introduce science to children at a young age in an entertaining way. This community service activity aims to introduce science to early childhood and increase children's abilities and interest in science. The target of this activity is children from middle-class to lower-class families that live in the area of the Rumah Pintar Mingguan (RPM) Kreatif Ampang. Five RPM volunteers and 31 children participated in this activity. This PKM activity was carried out through a simple science mini-practicum, by utilizing simple and inexpesive materials and tools that can be found easily in the surrounding environment. The main ingredients were baking soda and vinegar (acetic acid). The method used in this activity were a case study and hands-on practice. Two topics that are carried out on this practicum, namely the phenomenon of an erupting Merapi volcano and inflating a balloon without being blown up. This practice has the effect of increasing children's interest in and motivation for science, which is directly correlated with their increased comprehension of the concepts being demonstrated. Additionally, RPM decided to make this science practicum activity as a regular agenda item for the RPM community.